Comparative Analysis of 24-h Movement Behaviours in Non-Overweight and Overweight/Obese Children: Findings from the FAMIly Physical Activity, Sedentary Behaviour, and Sleep (FAMIPASS) - Sigmund, Erik; Voráčová, Jaroslava; Dygrýn, Jan; Vorlíček, Michal; Sigmundová, Dagmar (Children (Basel, Switzerland), 2024)
BACKGROUND: Childhood overweight and obesity are global health concerns associated with insufficient physical activity (PA), excessive sedentary behaviour (SB), and inadequate sleep. This study aimed to determine whether differences exist in 24 h movement behaviours between Czech non-overweight children and children with overweight/obesity aged 3-10 years, with respect to their gender, age, or family socioeconomic status (SES). METHODS: A total of 381 children (49.9% girls), aged 3-10 years, participated. Their PA, SB, and sleep were continuously monitored over a regular week using wrist-worn accelerometers. Weight status was determined by BMI z-scores, according to World Health Organization standards. SES was assessed using the Family Affluence Scale. RESULTS: Non-overweight children had averages of 414 min of PA, 472 min of SB, and 554 min of sleep per day, while children with overweight/obesity had averages of 392 min of PA, 503 min of SB, and 545 min of sleep. Non-overweight children engaged in significantly more PA (22 min per day; p = 0.014) and significantly less SB (31 min per day; p = 0.002) than children with overweight/obesity. No significant differences were found between the weight groups in gender distribution, age, family SES, or maternal and paternal obesity. CONCLUSIONS: Non-overweight children exhibited higher levels of PA and lower levels of SB compared to their counterparts with overweight/obesity, independent of gender, age, or family SES. These findings highlight an association between daily movement behaviours and weight status in young children. Further research is needed to explore the impact of modifying PA and SB on weight outcomes.
Keywords: socioeconomic status; physical activity; gender; sedentary; excessive body weight